Forming a single currency in ASEAN countries: a VAR analysis / Nor Azira Ismail - Ismail, Nor Azira (Research Management Institute (RMI), 2013)
The idea of this paper as title 'Forming a Single Currency in ASEAN Countries by applying VAR Analysis' is due to successful launch of the Euro in the early 1999 which make a common currency a particularly interesting option for region in ASEAN itself. More importantly, the recent regional financial crisis in ASEAN countries of 1997 has revealed vulnerabilities of exchange rate regime in the region. Furthermore, it has eroded the credibility of unilateral fixed exchange rate and correspondingly renewed calls for greater monetary integration and regional exchange rate stability in ASEAN. In addition, many researchers have advocated alternative exchange rate arrangement to enhance exchange rate stability. For instance, Williamson (1999) proposes a common basket peg among East Asian economies in his study. Meanwhile, Ogawa and Ito (2002) also advocate a basket beg to keep the real effective exchange rate stable. Beside, Kwan (1998) makes a proposal for formation of a yen bloc in East Asia and also McKinnon (2000) proposes to restore a dollar which based on exchange rate regime in East Asia while strengthening bank regulations.